PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA SENTRAL CAWANG HOTEL JAKARTA TIMUR - Sepriani, Muni; Sari, Ratna (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this study was to determine the partial and simultaneous influence of communication and work discipline on employee performance at the Sentral Cawang Hotel, East Jakarta. The method used was quantitative.. The sampling technique used saturated sampling and a sample of 61 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that communication has a significant effect on employee performance with a coefficient of determination value of 51.8% and the hypothesis test obtained t count > t table or (4.587 > 2.001). Work discipline has a significant effect on employee performance with a coefficient of determination value of 61.7% and hypothesis testing obtained t count > t table or (8.639 > 2.001). Communication and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 33.374 + 0.080X1 + 0.196X2. The coefficient of determination value is 82.7% while the remaining 17.3% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (84.318 > 3.156).